2003
DOI: 10.1029/2002je002018
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of the Mars Pathfinder alpha proton X‐ray spectrometer

Abstract: The chemical compositions of Martian rocks and soils examined with the alpha proton X‐ray spectrometer (APXS) during the Mars Pathfinder 1997 lander mission were not previously fully determined. Preliminary chemical results included major element abundances determined by the incomplete calibration of the X‐ray mode. The data collected from the alpha and proton detectors were not previously analyzed due to significant atmospheric contributions to the spectra. The backup instrument of the Pathfinder alpha proton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…Rock surfaces measured at the Mars Pathfinder landing site (MPF) (Rieder et al, 1997) are enriched in silica, which could be indicative of a silica-rich primary composition. However, recent recalibration of those results suggests that the high-silica rock surfaces are also rich in H 2 O, which could indicate a secondary origin of the silica-rich material (Foley et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Rock surfaces measured at the Mars Pathfinder landing site (MPF) (Rieder et al, 1997) are enriched in silica, which could be indicative of a silica-rich primary composition. However, recent recalibration of those results suggests that the high-silica rock surfaces are also rich in H 2 O, which could indicate a secondary origin of the silica-rich material (Foley et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Based on its MgO content, JM is more fractionated than most other martian rocks-of the analyses plotted in Fig. 3, only the basaltic shergottite Los Angeles (9), the rocks Wishstone and Champagne analyzed by the MERs (10), and the two estimated soil-free Pathfinder rock compositions (11,12) have similar or lower MgO contents.…”
mentioning
confidence: 99%
“…However, there are also regional and trace components in Martian soil, such as carbonate, chlorohydrocarbon, and glassy spherules identified at the Gale Crater (Blake et al 2013;Leshin et al 2013;Minitti et al 2013). In situ measurements of soil samples indicate that Martian soil contains approximately 43-45 wt% SiO 2 , 16-20 wt% FeO, 7-10 wt% Al 2 O 3 , 6-9 wt% MgO, 6-8 wt% CaO, 0.7-0.9 wt% P 2 O 5 , and 5-8 wt% SO 3 (Banin et al 1992;Foley et al 2003;Gellert et al 2004;Rieder et al 2004;Blake et al 2013). As shown in Table 1, compared to Martian soil, JMSS-1 has higher levels of SiO 2 (49.28 wt%) and Al 2 O 3 (13.64 wt%) and lower levels of SO 3 and P 2 O 5 (0.3 wt%).…”
Section: Comparison With Martian Soilmentioning
confidence: 99%
“…Physical weathering (e.g., impact events and wind abrasion) of a variety of intermediate to basic igneous rocks (basalts and probably basaltic andesites) is the presumed genesis of the majority of the soil, although minor chemical alterations to the source rocks and/or generated soil may occur (Wanke et al 2001;Foley et al 2003;Christensen et al 2004a;Morris et al 2004Morris et al , 2006aMcSween et al 2009). Data from ground-based landers/rovers and orbital spacecraft revealed that the Martian surface is dominated by basaltic soil composed primarily of pyroxene, plagioclase feldspar, and olivine, as well as minor amounts of Fe and Ti oxides (e.g., magnetite, ilmenite, and hematite) and alteration minerals (e.g., sulfates, phyllosilicates, and carbonates) (Yen et al 2005;Morris et al 2006a;Morris et al 2006b;McSween et al 2010;Bish et al 2013).…”
Section: Target Simulant and Raw Materials Selectionmentioning
confidence: 99%